Colorectal cancer prevention and intentions to use low-dose aspirin: A survey of 1000 U.S. adults aged 40–65. (April 2016) - Jensen, Jakob D.; Holton, Avery E.; Krakow, Melinda; Weaver, Jeremy; Donovan, Erin; Tavtigian, Sean
Highlights: Adults ( N = 1000) were surveyed to ascertain their knowledge of low-dose aspirin as a means of preventing colorectal cancer. Older, Black males were more receptive to initiating low-dose aspirin usage for the purpose of preventing colorectal cancer. Smokers, and those with a history of polyps, were more receptive to initiation for the purpose of preventing colorectal cancer. Self/response efficacy were the best psychosocial correlates of intention. Abstract: Objective: The Translating Research into Action (TRIA) study was initiated to gather dissemination information on emerging cancer control recommendations. Daily, low-dose aspirin has been identified as a promising means of preventing colorectal cancer, and stakeholders are already calling for research to facilitate dissemination. Thus, the current study sought to identify factors related to intention to use aspirin for colorectal cancer prevention. Methods: In April 2014, U.S. adults aged 40–65 ( N = 1000) were recruited to participate in a survey grounded in the health belief model. Results: Older, Black males were more likely to intend to use low-dose aspirin to prevent colorectal cancer. Smokers, and those with a history of polyps, were also more receptive to initiating daily, low-dose aspirin use. Five psychosocial factors were related to intention including self-efficacy, response efficacy, perceived barriers, perceived susceptibility to colorectal cancer, and cancer information overload. Conclusion: Initial campaigns/interventions designed to increase daily, low-dose aspirin for colorectal cancer prevention may be more effective if they target receptive populations (older, Black males) using messages informed by the health belief model.